Capability of Vitamin E as a Radioprotector in Suppressing DNA Damage Determined with Comet Assay - Darlina Darlina; Lusy Dahlia A.; Zubaidah Alatas; Teja Kisnanto; Mukh Syaifudin (Biosaintifika: Journal of Biology & Biology Education, 2017)
Radiation has a potent to damage cells. Radiation may act directly or indirectly on deoxyribonucleic acid (DNA) that results in the degeneration of tissues and necrotic, and thereby it needs a potent radioprotector to prevent these damages. Vitamin E is natural product known as an antioxidant which has potential as radioprotector. This research aimed to determine the capability of vitamin E with emphasized on the searching for its optimal concentration as radioprotector of DNA damage. This study used blood samples of healthy person irradiated with gamma rays at a dose of 6 Gy as the lethal dose to lymphocytes. The cocentrations of vitamin E from 0 to 0.8 mM was added into blood 15 minutes before irradiation. Isolation of lymphocytes was done using gradient centrifugation method. Evaluation on the capability of this compound in suppressing DNA damage was done by using alkaline Comet assay and data analysis was done using CaspLab program. The results show that addition of vitamin E could suppres these DNA damages and 0.8 mM of vitamin could reduce DNA damage up to 94.2%. We conclude that vitamin E effectively suppresed DNA damages induced by radiation. This information may benefit to the patient from negative impacts of radiotherapy.